SMA Kosgoro Bogor's Student Attendance Accountability Through Finger Print That Led to Appreciation - Lasrin, Herman (Jurnal Manajemen, 2024)
SMA Kosgoro Bogor uses fingerprint technology as a tool to improve accountability of student attendance and monitoring. The implementation of fingerprint technology has enabled the school to have detailed and automated information about student attendance. This article aims to explain how the use of the fingerprint system at SMA Kosgoro Bogor can improve student attendance accountability. The method used in this research is a descriptive qualitative method that produces descriptive data in the form of written or oral observations of people and observable behaviour. The data source of this research uses primary data sources and secondary data. The research subjects were all students of SMAS Kosgoro Bogor. One form of appreciation given is the provision of free tuition scholarships at the beginning of each month that meets predetermined criteria, such as consistent daily attendance, recorded in the school attendance system, designated as a nominee by the homeroom teacher, active in extracurricular activities, speaking well, and behaving politely.